Effect of anodising electrolyte on performance of AZ31 and AM60 magnesium alloys microarc anodic oxides. (November 2013) - Da Forno, A.; Bestetti, M.; Lecis, N.
Abstract : Various oxide film layers were grown onto AZ31 and AM60 magnesium alloy substrates by micro-arc anodic oxidation (MAO) in alkaline phosphate solutions with different additives such as silicate, aluminate and tetraborate. Surface morphologies and phase composition of the films were assessed by scanning electron microscopy (SEM) and X-ray diffraction (XRD) respectively. The adhesion strength of the anodic oxides was evaluated by scratch testing. The electrolyte composition affects the surface morphology and the adhesion of the oxides to the alloy substrates. The anodising solution consisting of phosphate, tetraborate and silicate produces a better oxides adhesion compared to those achieved in other electrolytic solutions.